A Study on Determination of Physio-Chemical Characteristics of Effluents: Analysis of Physico-Synthetic Parameters in Paper and Mash Industry Effluents (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Physico-synthetic parameters of the effluents from paper and mash industry had been examined. In this examination physico-substance parameters, for example, shading, smell, temperature, thickness, surface strain, consistency, alkalinity, acridity, chloride, hardness, absolute broke down solids, all out suspended strong, pH, conductance, sulfate, COD, BOD, had been dissected of the profluent gathered from the business ofpper and mash. Sodium and potassium components were broke down fire photometrically.